Biased technological progress and total factor productivity growth: From the perspective of China's renewable energy industry - Zhen, Wang; Xin-gang, Zhao; Ying, Zhou (Renewable & sustainable energy reviews, 2021)
With the decline in the intensity of subsidy policies, technological progress has become a critical factor in promoting the renewable energy industry's sustainable development. This paper estimates the direction and extent of biased technological progress in China's renewable energy industry from 2009 to 2018. On this basis, by constructing an accounting model for the growth rate of total factor productivity (TFP), this paper empirically analyzes the effects of different factors on TFP growth. The research results indicate that: (1) The TFP of China's renewable energy industry has dropped by 4.60% annually, and the growth of industrial output mainly relied on factor input rather than technological progress. (2) The technological progress and factor allocation of China's renewable energy industry generally show a bias towards the capital. At different stages of the industry's development, it presents different degrees of bias. (3) Technological progress is biased towards capital factor with a lower growth rate of factor efficiency, which hinders the growth of TFP in the renewable energy industry. •This paper reveals the driving mechanism for the development of China's renewable energy industry.•The technological progress and factor allocation of China's renewable energy industry are biased towards the capital.•Capital inefficiency is the fundamental reason for the reduction of TFP in the renewable energy industry.•Improving the level of independent R&D is the key to achieving China's renewable energy industry's sustainable development.